PENGARUH INFORMATION TECHNOLOGY INFRASTRUCTURE TERHADAP KNOWLEDGE SHARING INTENTION DI INDUSTRI RETAIL INDONESIA - Violivia Leony Johanesputri; Agus Gunawan; Yoke Pribadi Kornarius; Angela Caroline (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
Covid -19 has forced all industries to adapt in order to survive, especially in the retail industry. The retail industry can adapt if they do knowledge sharing so that all employees have the same knowledge. Retail need to provide a system that can help distribute knowledge to all employees. This system needs to be supported by technological advances to accelerate the process of distributing this knowledge. This explanatory type of research aims to determine the relationship and influence of information technology infrastructure (ITI) variables on knowledge sharing interest (KSI) variables in the Indonesian retail industry. The sampling technique used is purposive sampling with a sample of 173 respondents. The results showed that ITI and KSI had a strong relationship, namely 0.690 and an R-square value of 0.476, which means that ITI has a positive and significant effect on KSI.